Proses Penciptaan Manusia Perspektif Al-Qur’an dan Kontekstualitasnya dalam Materi Pelajaran Biologi - Fauzan, Mohd; Hitami, Munzir; Yusuf, Kadar M (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this research is to analyze the contextuality between the Qur'an and science regarding the process of human creation. This study used a qualitative method through literature study, using a reproductive health theory approach and mauḍu'î interpretation. The results and discussion of this study indicate that the process of creating humans after Prophet Adam went through reproduction, among the phases of which were nuṭfah, 'alaqah, muḍgah, making bones, forming muscles, then perfecting them by blowing the spirit into the best form. Whereas in science, according to Sadler, the phases are gametogonesis, the ovulation process to implantation, then the bilaminar gem disc, the embryonic period, up to the time of delivery. According to Dudek, they are prefertilization, weekly period, embryonic period, and organogenesis. This study concludes that the process of human creation in the Qur'an is in accordance with the findings of today's modern scientists. This study recommends that scientific verses be disclosed using scientific commentary books